2016
DOI: 10.18378/rebes.v6i3.4466
|View full text |Cite
|
Sign up to set email alerts
|

Análise epidemiológica de leishmaniose visceral em Municípios do Sertão Paraibano

Abstract: As Leishmanioses constituem um problema que afeta principalmente as pessoas mais pobres e com maior dificuldade de acesso aos serviços de saúde. No Brasil, a Leishmania chagasi é o principal agente etiológico. Objetivou-se analisar a incidência da LV em municípios da Nona Gerência Regional de Saúde do estado da Paraíba. O Estudo transversal retrospectivo, compreendido no período de 2010 a 2014, obtidos no Sistema de Informação de Agravos de Notificação (SINAN). Os dados foram analisados quanto ao número de cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0
4

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 4 publications
1
4
0
4
Order By: Relevance
“…This fact has also been found by other studies, which found percentages between 60 and 75%, pointing to greater male susceptibility to the disease. 13,[17][18][19][20] Hormonal factors and factors related to exposure to the vector have been held responsible for increased risk of infection in males. 11 People of brown race/skin color were the most affected, differently to what was reported by a study conducted in the municipality of Bauru, SP, where 49.3% of notified VL cases were among people of white race/skin color.…”
Section: Discussionmentioning
confidence: 99%
“…This fact has also been found by other studies, which found percentages between 60 and 75%, pointing to greater male susceptibility to the disease. 13,[17][18][19][20] Hormonal factors and factors related to exposure to the vector have been held responsible for increased risk of infection in males. 11 People of brown race/skin color were the most affected, differently to what was reported by a study conducted in the municipality of Bauru, SP, where 49.3% of notified VL cases were among people of white race/skin color.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, it was observed that in the state of Paraíba both HVL and CVL present expansions. According to some scholars, one of the factors for the process of expansion and transition of VL is the migration of the population from rural to urban areas (Barbosa, 2011;Teles, 2011;Lisboa et al, 2016). In the state of Paraíba it was observed that between the 2000 and 2010 censuses, the total population increased 3,443,825 to 3,766,528 inhabitants.…”
Section: Discussionmentioning
confidence: 99%
“…O diagnóstico definitivo da LV envolve a demonstração do parasita, obtida por diversas técnicas parasitológicas de pesquisa direta e indireta, dentre as quais o teste diagnóstico mais confiável é a observação direta do parasita em esfregaços da medula óssea ou linfonodos (NORÕES et al, 2015;LISBOA et al, 2016). No caso do paciente…”
Section: Introductionunclassified